Considerations regarding the Morlachs migrations from Dalmatia to Istria and the Venetian settlement policy during the 16th century - Caciur, Dana (Balcanica Posnaniensia. Acta et studia, 2015)
The Turkish offensive in the Balkans often determined various human groups to search for a new life outside the borders of the Ottoman Empire. In the Dalmatian hinterland, administrated by Venice since the beginning of 16th century, the Morlachs are those who, together with Serbs, Croatians, Bosnians, etc. chose to accept the Venetian protection against the non-Christian danger. On its side, St. Mark′s Republic needed more and more new people to repopulate various regions that had hardly been affected by wars, plagues and drought. During the 16th century <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Serenissima established the rules of internal migrations (from one region to another of <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Stato da Mar) and its settlement policy for the poorly inhabited areas and their new colonists. The encouragement and the development of the population transfer from Dalmatia to Istria represented an aspect of the Venetian policy in balancing the demography of the state. Arrived from the inner Balkans, the Morlachs accepted quite often to settle in south – western Istria, because the benefits and the exemptions offered by the Republic were not to be ignored: exemptions from fees for using public pasturelands, the right to build settlements in empty spaces, exemptions from fees for transport or reductions from some of the administrative taxes. Even if these benefits were temporary or permanent, they used to increase the number of Morlach migrations from Dalmatia in Istria. In effect, as the documents attest, during the 16th century plenty of Morlach settlements appeared in the hinterland of the Istrian cities, like: Rovigno, Umago, Pinguente, Montona, Cittanova, Villanova, Raspo, Parenzo etc. Despite the fact that sometimes the Morlachs chose to leave the new settlements and turn back in <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Turchia, the numerous settlements colonized and inhabited by them justify, up to some extent, the existence of an <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Istrian Morlacchia.